Maximizing Marketing Effectiveness through Knowledge Management Strategies - Haris, Abdul (Paradoks : Jurnal Ilmu Ekonomi, 2024)
This study aims to investigate the critical nexus between knowledge management (KM) strategies and marketing effectiveness, aiming to shed light on key insights drawn from a systematic literature review. The research design and methodology involve a comprehensive review of existing literature in marketing and knowledge management, synthesizing insights from various studies to elucidate the role of KM in enhancing marketing performance across diverse industries and organizational contexts. The findings and discussion underscore the pivotal role of KM strategies in maximizing marketing effectiveness, emphasizing the positive impact of robust KM processes on key performance metrics such as customer satisfaction, brand loyalty, and competitive advantage. Additionally, the integration of technological enablers such as data analytics, social media monitoring, and artificial intelligence is highlighted as essential for augmenting the effectiveness of KM strategies, enabling organizations to derive actionable insights, optimize marketing campaigns, and personalize customer experiences. The implications of this study are twofold. Firstly, for academia, the study contributes to advancing knowledge in marketing and knowledge management by synthesizing insights from existing literature and identifying avenues for future research. Secondly, for practice, the findings offer actionable insights for organizations seeking to enhance their marketing effectiveness through knowledge management strategies. By recognizing the critical role of KM in gaining a competitive edge, fostering innovation, and achieving sustainable growth, organizations can prioritize investments in KM processes, technologies, and organizational culture conducive to knowledge sharing and collaboration.